2010
DOI: 10.1111/j.1365-2982.2010.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of cellular components of the enteric nervous system in the normal human gastrointestinal tract - report on behalf of the Gastro 2009 International Working Group

Abstract: The aim of this report was to summarize all relevant available published quantitative data for elements of the human enteric nervous system (neuronal cell bodies, glial cells, and nerve fibers) from the perspective of the practicing pathologist. Forty studies meeting inclusion criteria were systematically reviewed with data tabulated in detail and discussed in the context of methodological variations and limitations. The results reveal a lack of concordance between observations of different investigators resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 54 publications
3
84
0
2
Order By: Relevance
“…In addition, patients with symptoms of severe dysmotility who underwent intestinal resection within the same time-frame were also identified. These patients were not considered for laparoscopic biopsy since full-thickness intestinal wall tissue was already available for analysis and thereby histopathological classification (14)(15)(16). Identified patients represent the majority of cases of suspected CIPO/ED in the most southern parts of Sweden.…”
Section: Subjectsmentioning
confidence: 99%
“…In addition, patients with symptoms of severe dysmotility who underwent intestinal resection within the same time-frame were also identified. These patients were not considered for laparoscopic biopsy since full-thickness intestinal wall tissue was already available for analysis and thereby histopathological classification (14)(15)(16). Identified patients represent the majority of cases of suspected CIPO/ED in the most southern parts of Sweden.…”
Section: Subjectsmentioning
confidence: 99%
“…In a previous article, this group had defined techniques for histopathological workup, interpretation, and reporting of intestinal neuromuscular disorders (3). A systematic review by the IWG revealed a lack of concordance in the quantitative assessment for elements of the enteric nervous system (ENS) (4).…”
mentioning
confidence: 99%
“…The 3 recent articles (2)(3)(4) by the IWG have tried to collate present knowledge in this field. Despite these comprehensive publications, the use of inaccurate terminology and vague diagnostic criteria remain common (9).…”
mentioning
confidence: 99%
“…Part of the apparent change in cellularity is due to agerelated changes in the size and shape of ganglion cells and the amount of intervening neuropil. Even if the number of ganglion cells per ganglion remains stable with age, individual ganglion cell somata enlarge, [21][22][23] which can influence the number of cytoplasmic profiles likely to be transected in a section of given thickness. This may be one reason for the age-related decline in submucosal ganglion size during infancy and early childhood.…”
Section: Inappropriate Extrapolation Of 1990 Frankfurt Consensus or 2mentioning
confidence: 99%
“…However, many studies have shown that counting ganglion cells, like many quantitative exercises in surgical pathology, is extremely vulnerable to interobserver bias. 20,21,29 In 1999, a group of pathologists, which included Meier-Ruge, Coerdt, and other experienced IND B diagnosticians, examined their own interobserver variability. 5 They observed that their ''j values were close to the zero value expected by chance for the diagnoses normal and IND B'' and concluded that ''with current knowledge, rectal biopsy for diagnostic purposes should only be performed in constipated children for diagnosis of Hirschsprung's disease.''…”
Section: Interobserver Variabilitymentioning
confidence: 99%